ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MOTIVASI KERJA PEGAWAI PADA UPT. PENCEGAHAN DAN PENANGGULANGAN KEBAKARAN DINAS PEKERJAAN UMUM KABUPATEN KUTAI TIMUR - Muis, Abdul (PREDIKSI, 2016)
This study aims to level of employee motivation and the factors that influence the motivation of employees working on the UPT. Fire Prevention and Public Works Department of East Kutai. This study uses qualitative descriptive approach.The results showed that the factors that are the focus in this study provide a good influence on work motivation, where the compensation factor of 85.3%, a promotion factor of 83.9%, work environment factors of 88.7% and employee development factors amounted to 82.5%.The results showed also that the average percentage of all the factors working simultaneously on the motivation of employees amounted to 85.1%. This means that factors such compensation, promotion, work environment and employee development simultaneously provide a good influence on employee motivation.